Biological-fishery aspects of Peruvian silverside (Odontesthes regia regia) in the harbor of Ilo during 1996-1998 - Treviño, Hugo (1999)
The biological and fishery aspects of the Peruvian silverside (Odontesthes regia regia) in Ilo were analyzed, since January 1996 to September 1998. The catches were three times higher (72,76 t) between 1996 to1997, while with the warming of "El Niño" in 1998 these decreased to 0,62 t. During "El Niño 1997-98" event the population showed also a series of changes in distribution, reproduction, and composition of the diet. These changes were associated to the incursion of superficial subtropical water.